HEALTH RISK ANALYSIS OF EXPOSURE NO2 AND SO2 AT STREET VENDORS IN KAMBANG IWAK AREA PALEMBANG CITY - Januarsi, Riska; Sunarsih, Elvi (HEARTY, 2024)
Kambang Iwak Palembang city is park the city that always is crowded passed by vehicles general nor vehicle personal with density and activity then enough traffic tall. High vehicle volume contribute give rise to various pollutant gas emissions, including NO2 and SO2 which can endanger health man If reach concentration certain. Objective study for analyze risk health consequence exposure to NO2 and SO2 to street vendors in Kambang Iwak area Palembang city. Method study apply design study descriptive with approach quantitative as well as use environmental health risk analysis. Population study that is street vendors in Kambang Iwak totaling 150 people and a sample of 109 people was counted use formula slovin and determined through technique purposive sampling. Data analysis using analysis univariate and analysis risk health environment. Average concentrations of NO2 and SO2 at 3 points measurement namely 0.007 mg/m3 and 0.012 mg/m3, concentrations the No exceed mark standard quality determined by the Regulations Government No. 22 of 2021. As many as 58.2% of respondents own NO2 intake value>0.00191 mg/m3, and SO2 intake>0.00327 mg/m3. Whole respondents show RQ value<1 for non-carcinogenic exposure. No There is risk happen disturbance non-carcinogenic health consequence exposure to NO2 and SO2 to all over street vendors in Kambang Iwak area Palembang city.